Is pollen size a robust proxy for moisture availability? - Jardine, Phillip E.; Lomax, Barry H. (Elsevier, 2017)
The development of well-constrained palaeo-proxies that enable the reconstruction of past climate change is becoming an ever more important field of scientific enquiry within the palaeobotanical community, with the potential to deliver broader impacts linked to understanding of future anthropogenic climate change. One of the major uncertainties in predicting climate change is how the hydrological cycle will respond to future warming. Griener and Warny (2015, Review of Palaeobotany and Palynology 221, 138-143) suggested that pollen size might be a useful proxy for tracking moisture availability, as pollen size appears to be negatively correlated with moisture. Given the long fossil record of pollen and spores such a proxy would have broad scope and the potential to deliver much needed information. Here we set out to fully evaluate and test the robustness of this proxy. We focus on a number of a key issues: controls on pollen size, data analysis, and finally proxy validation. Using this approach we find that there is little theoretical or empirical support for the original relationship proposed by Griener and Warny. Consequently it is currently premature to use pollen size as a moisture availability proxy in the fossil record. However, we recognise that the technique may have potential and conclude by offering a series of recommendations that would rigorously assess and test for a relationship between pollen size and moisture availability.